Ultrasound of Small Nerves - Meng, Stefan; Platzgummer, Hannes; Loizides, Alexander; Chang, Ke-Vin; Gruber, Hannes (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Nerve ultrasound has become an integral part of the diagnostic workup of peripheral neuropathies. Especially in the examination of small nerves, ultrasound provides superior image quality by using high frequency transducers. For a selection of small nerves, this article summarizes the local anatomy and common pathologies and offers simple instructions for determining their location with ultrasound including some cases with pathologies. This selection of nerves comprises the great auricular nerve, the supraclavicular nerves, the suprascapular nerve, the medial antebrachial cutaneous nerve, the lateral antebrachial cutaneous nerve, the palmar cutaneous branch of the median nerve, the long thoracic nerve, the intercostobrachial nerve, the posterior cutaneous nerve, the infrapatellar branch of the saphenous nerve, the medial calcaneal nerve, and the deep peroneal nerve at the ankle. Following our recommendations, these nerves can be swiftly located and tracked along their course to the site of the pathology.Der Nervenultraschall ist zu einem festen Bestandteil der Diagnostik von peripheren Neuropathien geworden. Insbesondere bei der Untersuchung kleiner Nerven bietet der Ultraschall durch die Verwendung von Hochfrequenzschallköpfen eine überlegene Bildqualität. Für eine Auswahl kleiner Nerven fasst dieser Artikel die lokale Anatomie und häufige Pathologien zusammen und bietet einfache Anweisungen zur Bestimmung ihrer Lage mittels Ultraschalls, einschließlich einiger Fälle mit Pathologien. Diese Auswahl an Nerven umfasst den Nervus auricularis magnus, den Nervus supraclavicularis, den Nervus suprascapularis, den Nervus cutanus antebrachii medialis, den Nervus cutanus antebrachii lateralis, den Ramus palmaris des Nervus medianus, den Nervus thoracicus longus, den Nervus intercostobrachialis, den Nervus cutaneus femoris posterior, den Ramus infrapatellaris des Nervus saphenus, den Nervus calcaneus medialis und den tiefen Nervus peroneus profundus am Sprunggelenk. Mit unserer Empfehlung können diese Nerven schnell lokalisiert und entlang ihres Verlaufs bis zum Ort der Pathologie verfolgt werden.